Anemia in the pediatric patient - Gallagher, Patrick G. (Blood, 2022)
The World Health Organization estimates that approximately a quarter of the world's population suffers from anemia, including almost half of preschool-age children. Globally, iron deficiency anemia is the most common cause of anemia. Other important causes of anemia in children are hemoglobinopathies, infection, and other chronic diseases. Anemia is associated with increased morbidity, including neurologic complications, increased risk of low birth weight, infection, and heart failure, as well as increased mortality. When approaching a child with anemia, detailed historical information, particularly diet, environmental exposures, and family history, often yield important clues to the diagnosis. Dysmorphic features on physical examination may indicate syndromic causes of anemia. Diagnostic testing involves a stepwise approach utilizing various laboratory techniques. The increasing availability of genetic testing is providing new mechanistic insights into inherited anemias and allowing diagnosis in many previously undiagnosed cases. Population-based approaches are being taken to address nutritional anemias. Novel pharmacologic agents and advances in gene therapy-based therapeutics have the potential to ameliorate anemia-associated disease and provide treatment strategies even in the most difficult and complex cases. •Anemia is a major global burden, affecting almost 2 billion people worldwide, particularly infants and young children.•Population approaches are being employed to treat dietary anemia, and therapeutic advances are improving care for inherited anemias. [Display omitted]